PELAKSANAAN FUNGSI DINAS KOPERASI, USAHA KECIL DAN MENENGAH, PERINDUSTRIAN DAN PERDAGANGAN DI PASAR TRADISIONAL KELURAHAN SOREK SATU KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN TAHUN 2020-2021 - Simamora, Rixon Paulinus; ', Wazni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The development of traditional markets in Sorek Satu Village, Pangkalan Kuras District, Pelalawan Regency is increasingly rapid. So it is necessary to carry out good government management to meet the needs of the community through the policies and strategies implemented. The Department of Cooperatives, Small and Medium Enterprises, Industry and Trade is required to carry out its functions in order to change the public's view of traditional markets which seem dirty and seedy. The condition of this traditional market is poorly maintained, characterized by poor cleanliness, poor orderliness, facilities that are not well maintained, and the establishment of new stalls outside the market area which greatly disrupts the market arrangement. The research uses the theory of government functions, namely service, empowerment and development by Taliziduhu Ndraha. The research approach used is a qualitative approach. This type of research is descriptive. The research location is at the Traditional Market, Sorek Satu Village, Pangkalan Kuras District, Pelalawan Regency. Types and sources of research data are divided into primary data obtained through interviews with informants and secondary data in the form of supporting data related to the market. The results of this research found that the function of the Department of Cooperatives, Small and Medium Enterprises, Industry and Trade was not running well. It is characterized by not maintaining the market buildings, dirty market conditions, a lack of cleaning staff, many traders who do not comply with the rules and there is no regular guidance for market managers and traders. Keywords: Traditional Markets, government functions, services, empowerment and development.